How User-Generated Content Influences Hotel Booking Decisions on Traveloka - Ambarin Syaqufa; Nurrani Kusumawati (Mandalika Institute, 2024)
Digital transformation has become a critical focus worldwide, including the rapid adoption of innovative technologies with diverse applications across various markets and industries. In the midst of emerging features from the development of these applications, experiences shared by other customers through UGC are perceived as more trustworthy than brand-promoted content compared to content from social media, which has key factors including perceived credibility, usefulness, homophily, and information quality. UGC has fundamentally transformed the travel industry by changing how information is obtained and shared, affecting how tourists plan their trips and impacting customer satisfaction and purchase decisions like Traveloka. This study aims to explore the relationship between UGC factors, customer attitude towards UGC, and customer trustworthiness for utility in purchase decisions in the hotel sector in Traveloka. This research adopts a comprehensive approach by combining qualitative and quantitative analysis. Qualitative data was collected by analyzing automatic coding techniques with the NVivo tool. Meanwhile, quantitative data was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. In the qualitative stage, the research targeted travel enthusiasts who have booked hotels on OTA platforms, especially Traveloka users, with a minimum number of respondents of 12, and in the quantitative method, the minimum number of respondents was 200. The qualitative stage also explored an additional variable, perceived risk, which was further analyzed quantitatively in relation to attitude towards UGC. The findings of this study emphasize the significant impact of perceived reliability, perceived usefulness, information quality, perceived homophily, and perceived risk that influence attitude towards UGC for utility towards purchase decisions in the hotel sector. This research provides an understanding of the new role of several factors in UGC, explores their impact on attitude towards UGC and its use in hotel purchase decisions, and provides valuable guidance for optimizing strategies and maximizing the potential of UGC features in the travel industry in the hotel sector.